Solomon [videorecording (DVD)] - Cross, Ben; Fox, Vivica A., 1964-; Sydow, Max von, 1929-2020 (Dreamscape Media, 2023)
The story of Solomon, King of Israel, follows him as he falls in love with a beautiful queen and falls into a deep depression upon her departure, threatening his kingdom.